Podmiot feministyczny w koncepcjach Luce Irigaray, Julii Kristevy oraz Donny Haraway - Jaxa-Rożen, Hanna (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
Post-modernist debate focuses around the concept of the world and man presented by the philosophy described as the Enlightenment, Modernist or modern philosophy. At its culmination is the paradigm of knowledge developed by Kant and Descartes. The feminist theory of emancipation could not ignore the transformation reflected in every realm of cultural reality. The belief in a monolithic subject free from limitations has collapsed, as a result of events over the past few centuries and has left only the melancholy of uprooting. Feminism, particularly its second wave, has also joined the dispute on the shape of a new subjectivity. This discourse offers more than just a different outlook upon man, but also the reflection that points out to all the difficulties related to the discussion of the subject.
The feminist subject in the concepts of LuceIrigaray, Julia Kristeva and Donna Haraway